Thematic Mapping of Policy Documents Citing on Library and Information Science and Health Research - Ibrahim, Cecep; Handoyono, Susilo Teguh; Kangko, Danang Dwijo; Kurnianingsih, Indah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
Research in Library and Information Science (LIS) and Health has substantial applicability, including its use as a reference in the development of policy documents. This study aims to conduct a thematic mapping of policy documents that draw upon LIS and Health research. Using the Latent Dirichlet Allocation (LDA) method and Python-based machine learning, the research followed stages of data collection, filtering, processing, and analysis. The findings show that the Journal of Health Communication is the most frequently cited journal, with 1,756 citations. The United States emerges as the country that most extensively incorporates LIS and Health research into policy documents, accounting for 1,181 citations. The Centers for Disease Control and Prevention (CDC) is identified as the institution producing the highest number of policy documents referencing LIS and Health research, with 840 publications. The peak year for such publications was 2019, with a total of 384 documents. Thematic mapping reveals five dominant topics in these policy documents: Health Prevention, Youth Health, Science Dissemination, Risk Evaluation, and Development Strategies. The study highlights that LIS and Health research plays not only an academic role but also serves as a normative and strategic foundation for national policy formulation. Future research may apply similar methods to other disciplinary domains or conduct longitudinal analyses to identify thematic developments in policy documents over time.